The effect of aqueous extracts of selected Philippine soft corals to the behavior and mortality of tilapia (Oreochromis sp.) fry. - Celis, Juliet Katindoy
The ichthyotoxicity of crude aqueous extracts from four (4) species of soft corals collected in the reef fiat of Talisay Cove, Taklong, Nueva Valencia, Guimaras, was investigated within a 48-hour assay period. These soft corals were Sinularia sp., Pachyclavularia sp., Xenia sp., and nephthea sp. All caused mortality to tilapia (oreochromis sp.) fry. Sinularia sp. was the most toxic causing 100 mortality at 10 ppt. within 4 hours after exposure followed by Pachyclavuria sp. at 10 ppt. in 24 hours. Extracts from Xenia sp. and Nethea sp. were not as toxic., The sublethal effects of the extracts varied from disturbed swimming movements to surfacing or settling at the bottom behavior and, abnormal, movement, fin activity and response to visual stimulus which are all indicative of avoidance response and stress in the test organism.